A comprehensive review summarizing the recent biomedical applications of functionalized carbon nanofibers. Issue 11 (21st March 2021) - Abdo, Ghada G.; Zagho, Moustafa M.; Al Moustafa, Ala‐Eddin; Khalil, Ashraf; Elzatahry, Ahmed A.
Abstract: Since the discovery and fabrication of carbon nanofibers (CNFs) over a decade ago, scientists foster to discover novel myriad potential applications for this material in both biomedicine and industry. The unique economic viability, mechanical, electrical, optical, thermal, and structural properties of CNFs led to their rapid emergence. CNFs become an artificial intelligence platform for different uses, including a wide range of biomedical applications. Furthermore, CNFs have exceptionally large surface areas that make them flexible for tailoring and functionalization on demand. This review highlights the recent progress and achievements of CNFs in a wide range of biomedical fields, including cancer therapy, biosensing, tissue engineering, and wound dressing. Besides the synthetic techniques of CNFs, their potential toxicity and limitations, as biomaterials in real clinical settings, will be presented. This review discusses CNF's future investigations in other biomedical fields, including gene delivery and bioimaging and CNFs risk assessment. Abstract :